Pd supported on 3D graphene aerogel as potential electrocatalyst for alkaline direct methanol fuel cells. (2021) - Sahoo, Bibhuti Bhusan; Biswal, Kiranmayee; Jena, Archana; Naik, Brundabana; Nayak, Nimai C.; Dash, Barada P.; Mahanto, Bhabani Sankar; Soam, Ankur; Sahoo, Prasanta Kumar
Abstract: Direct methanol fuel cells (DMFCs) have been shown potential interest in several portable electronics for "green" power generation, however their large-scale commercial production are mostly hampered due to the low activity and high cost of the anode catalysts. In the present study, we report a facile, environmentally friendly, and cost-effective Pd supported on 3D graphene aerogel (Pd/GA) by one step freeze-casting process. The as-synthesized Pd/GA was broadly characterized by XRD, Raman, SEM, and TEM. Morphology observations show that 3D-porous cellular structure of Pd/GA with uniform distribution of 10 nm Pd nanoparticles on the surface of graphene sheets. Based on structural merits, the performance of Pd/GA has been investigated as an anode catalyst for alkaline DMFCs. Pd/GA catalyst shows significantly superior electrocatalytic performance, abnormally high poison tolerance, and stability as compared to the conventional Pd/ carbon black (Vulcan XC-72R) with the same loading (∼20%) of Pd.The superior electrocatalytic performance of Pd/GA towards methanol oxidation can be used in practical application as a promising anode material for DMFCs.